Pyrrolo[3, 2-b]pyrrole-based fused-ring electron acceptors with strong near-infrared absorption beyond 1000 nm. (November 2021) - Wang, Zemin; Jia, Boyu; Cai, Guilong; Wang, Jiayu; Li, Yawen; Xue, Peiyao; Lu, Xinhui; Lin, Yuze; Wang, Guojie; Zhan, Xiaowei
Abstract: We present the first report incorporating strongly electron-donating moiety pyrrolo[3, 2- b ]pyrrole into fused-ring electron acceptors, and design and synthesize two narrow-bandgap nonfullerene acceptor isomers PPIC1 and PPIC2. These two molecules bear the same electron-withdrawing terminal groups and isomeric eight-fused-ring cores. The two compounds exhibit strong light-harvesting ability in the near-infrared region beyond 1000 nm. Compared with the symmetric PPIC2, the asymmetrical PPIC1 shows remarkably blue-shifted absorption, wider bandgap, down-shifted highest occupied molecular orbital, up-shifted lowest unoccupied molecular orbital, and lower electron mobility. Paired with the classical polymer donor PTB7-Th, PPIC1-based photovoltaic devices exhibit higher open-circuit voltage, short-circuit current and efficiency than the PPIC2-based devices. Graphical abstract: Image 1 Highlights: Pyrrolo[3, 2- b ]pyrrole-based fused-ring electron acceptor isomers PPIC1 and PPIC2 are designed. Two isomers exhibit strong near-infrared absorption beyond 1000 nm. The asymmetrical PPIC1 shows better photovoltaic performance than the symmetric PPIC2.